2017
DOI: 10.1021/acs.energyfuels.7b02080
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conversion ofChlamydomonasto Hydrocarbons via the Ethanol-Assisted Liquefaction and Hydrotreating Processes

Abstract: Ethanol-assisted liquefaction followed by a hydrotreating process has been applied to the microalgal biomass of Chlamydomonas. The intent of the research was to develop process technology to convert microalgae into drop-in fuels. The operation conditions of the ethanol-assisted liquefaction were optimized using the following variables: reaction temperatures (200−290 °C), ethanol concentration (10−90 vol. %), residence time (0.5−2 h), and the catalyst (SO 4 2− /ZrO 2 ). The application of a higher ethanol conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…During HTL, the feedstock is decomposed to form bio-crude oil that is sometimes called bio-oil, biochar, and gases at a moderate temperature of 280-450 • C, under an elevated pressure of 10-25 MPa, and in a water environment with a residence time typically in the range of 5-90 min [14]. Because the trend of the increase in biofuels production and consumption worldwide, further upgrading the bio-oil to biodiesel and green diesel are of interest [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During HTL, the feedstock is decomposed to form bio-crude oil that is sometimes called bio-oil, biochar, and gases at a moderate temperature of 280-450 • C, under an elevated pressure of 10-25 MPa, and in a water environment with a residence time typically in the range of 5-90 min [14]. Because the trend of the increase in biofuels production and consumption worldwide, further upgrading the bio-oil to biodiesel and green diesel are of interest [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of HTL of manure include: (1) Wet manure can be converted directly without the need of an energy-intensive drying process [19]; (2) HTL simultaneously treats and sterilizes the wastes; and (3) the bio-crude oil often possesses a higher energy content (ranging 21-35 MJ/kg) than original feedstock (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) MJ/kg) [20]. Comprehensive review of this topic can be found in the literature [11,21].…”
Section: Introductionmentioning
confidence: 99%
“…The authors attributed the higher activity to a lower site density on the face-centered cubic α-MoC 1– x /CNF, making the Mo atoms at the surface of the α-MoC 1– x phase more accessible for a large reactant. Mo 2 C supported on biochar for the HDO reaction has been reported by Zhang et al who showed that nonpolar solvents such as hexane enhance HDO more than polar solvents such as ethanol. Ochoa et al reported that high carburization temperature (≥650 °C) and low heating rates (1 °C/min) gave the highest yield of β-Mo 2 C and the corresponding highest catalyst activity.…”
Section: Introductionmentioning
confidence: 79%
“…In contrast, the use of hydrocarbon solvents could inhibit unwanted side reactions involving reactive radicals, which was in accordance with a previous study 45 on the dealkylation of 4-propylphenol. Zhang et al 47 reported a higher promotion of nonpolar solvents (e.g., hexane) over polar solvents (e.g., ethanol) on the HDO reaction when using Mo 2 C catalysts. The catalyst exhibited comparable activity in toluene or dodecane as a solvent but was less active in benzene.…”
Section: = × Conversion (Mol %)mentioning
confidence: 99%